2005
DOI: 10.1597/04-043r.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment in Children and Adolescents with a Craniofacial Anomaly: Age and Sex Patterns

Abstract: Most children with CFAs do not appear to experience psychosocial adjustment problems. Although elevated risk may be seen for certain problems, this group may be protected in other areas. Research identifying the mechanisms responsible for varying age and sex patterns of adjustment is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 25 publications
4
44
2
4
Order By: Relevance
“…These data corroborate the fi ndings of Ha et al (2013), Hunt et al (2005), Murray et al (2010), and Pope and Snyder (2005), who identifi ed clinical indications of anxiety/depression and attention problems in preschool children with orofacial clefts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data corroborate the fi ndings of Ha et al (2013), Hunt et al (2005), Murray et al (2010), and Pope and Snyder (2005), who identifi ed clinical indications of anxiety/depression and attention problems in preschool children with orofacial clefts.…”
Section: Discussionsupporting
confidence: 89%
“…This fi nding is supported by the study by Murray et al (2010), which found increased risk for socioemotional diffi culties in children with orofacial clefts, with indicators of anxious, introspective and depressed behaviors, as well as diffi culties in social interactions, typical of internalizing behaviors. Another study that confi rms the results found is that of Pope and Snyder (2005), in which clinical scores for isolation problems were observed in children with craniofacial anomalies in the 2 to 3 years age group and internalizing problems, such as attention and thought problems and introversion, in the 4 years age group.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The type of attentiveness that was assessed is not always specified, and is done by assessing the behavior of children; [24][25][26][27][28][29] other studies use individual tests to evaluate a specific type of attention. [30][31][32][33] Attention difficulties have been reported in subjects with reading impairment, 34 dyslexia, 35 aphasia, 36 sclerosis, 37 ADHD, 38 APD, 39 sleep deprivation,40 and cleft lip and palate.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Attention difficulties have been reported in subjects with reading impairment, 34 dyslexia, 35 aphasia, 36 sclerosis, 37 ADHD, 38 APD, 39 sleep deprivation,40 and cleft lip and palate. 32,28 Studies relating sustained auditory attentiveness and cleft lip and palate were not found in our review; we thus tried to correlate this study with those that included subjects with a history of recurring otitis. [9][10][11][12][13] We were aware that these studies were subject to methodological issues, including the retrospective studies that contain biases and imprecise methods for detecting OME.…”
Section: Discussionmentioning
confidence: 99%